The Foot Orthoses versus Hip eXercises (FOHX) trial for patellofemoral pain: a protocol for a randomized clinical trial to determine if foot mobility is associated with better outcomes from foot orthoses. Issue 1 (December 2017) - Matthews, Mark; Rathleff, Michael; Claus, Andrew; McPoil, Tom; Nee, Robert; Crossley, Kay; Kasza, Jessica; Paul, Sanjoy; Mellor, Rebecca; Vicenzino, Bill
Abstract Background Patellofemoral pain (PFP) is a prevalent, often recalcitrant and multifactorial knee pain condition. One method to optimize treatment outcome is to tailor treatments to the patient's presenting characteristics. Foot orthoses and hip exercises are two such treatments for PFP with proven efficacy yet target different ends of the lower limb with different proposed mechanisms of effect. These treatments have not been compared head-to-head, so there is a dearth of evidence for which to use clinically. Only foot orthoses have been explored for identifying patient characteristics that might predict a beneficial effect with either of these two treatments. Preliminary evidence suggests patients will do well with foot orthoses if they have a midfoot width in weight bearing that is ≥ 11 mm more than in non-weight bearing, but this has yet to be verified in a study that includes a comparator treatment and an adequate sample size. This trial will determine if: (i) hip exercises are more efficacious than foot orthoses, and (ii) greater midfoot width mobility will be associated with success with foot orthoses, when compared to hip exercises. Methods Two hundred and twenty participants, aged 18–40 years, with a clinical diagnosis of PFP will be randomly allocated with a 1:1 ratio to receive foot orthoses or progressive resisted hip exercises, and stratified into two subgroups based on their presenting midfoot width mobility (high mobility defined as ≥11 mm). The primary outcome will be a 7-point Likert scale for global rating of change. All analyses will be conducted on an intention-to-treat basis using regression models. Discussion This trial is designed to compare the efficacy of foot orthoses versus hip exercise, as well as to determine if high midfoot width mobility is associated with better outcomes with foot orthoses when compared to hip exercises. Results of this trial will assist clinicians in optimising the management of those with PFP by testing whether a simple measure of midfoot width mobility can help to determine which patients are most likely to benefit from foot orthoses. Trial registration This trial is registered on the Australian New Zealand Clinical Trials Register (ACTRN12614000260628 )